Wikipedia and Cryptocurrencies: Interplay Between Collective Attention and Market Performance - ElBahrawy, Abeer; Alessandretti, Laura; Baronchelli, Andrea (Frontiers in Blockchain, 2019)
The production and consumption of information about Bitcoin and other digital-, or crypto- , currencies have grown together with their market capitalization. However, a systematic investigation of the relationship between online attention and market dynamics across multiple digital currencies is still lacking. Here, we quantify the interplay between the attention towards digital currencies in Wikipedia and their market performance. We consider the entire edit history of currency-related pages and their view history from July 2015. First, we quantify the evolution of the cryptocurrency presence in Wikipedia by analyzing the editorial activity and the network of co-edited pages. We find that a small community of tightly connected editors is responsible for most of the production of information about cryptocurrencies in Wikipedia. Then, we show that a simple trading strategy informed by Wikipedia views performs better than baseline strategies, in terms of returns on investment, for most of the covered period although the ‘buy and hold strategy’ dominates during the periods of explosive market expansion. Our results contribute to the recent literature on the interplay between online information and investment markets, and we anticipate it will be of interest for researchers as well as investors.